THE FACTORS INFLUENCING SAFETY OF PENAL CORRECTION SYSTEM - Scherbakov, Andrey (Administrative and Criminal Justice, 2018)
In article the general and special factors exerting impact on safety of a penal correction system are considered (Further – penal correction system). Relying on the different points of view stated in science, results of the conducted research, supplementing and developing them, the author considers in more detail and represents the system of factors of the penal correction systems exerting impact on safety.